Mobiles & ICT Based Interventions for Learning Difficulties in Geometry - Galitskaya, Viktoriya; Drigas, Athanasios (International Journal of Engineering Pedagogy (iJEP), 2023)
The difficulty faced by students in Geometry (ageometria) is a relatively new learning difficulty that has not been extensively explored. Early detection, as well as intervention, is very important. Students with dyslexia, like all students with special learning difficulties, face difficulties in working memory. In addition, solving a geometric problem requires comprehension of pronunciation (in which students with dyslexia lag) and numerical processing (in which students with dyscalculia lag). For this reason, this article presents interventions aimed at improving working memory or improving reading or numerical skills, with the help of new technologies.